Virtual Homeland? : Reading the Music on Offer on a Particular Web Page - Senjković, Reana (Array, 2005)
The article analyses 68 songs from the free download music offer on a particular web page designed for Croatian-speaking users. The selection of songs is taken as a specific intersection of fantasy images and discursive forms, in which one of the contemporary Croatian cultural imaginings is contested. It is compared with imaginings from the last decade of the 20th century, which were the product of the socio-political elite's strategy and absorbed from the official media's offer during the 1991-5 war in Croatia.